2016
DOI: 10.3892/etm.2016.3931
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect of TUSPLV on recurrent varicocele

Abstract: The aim of the study was to analyze the treatment effect of transumbilical single-port laparoscopic varicocelectomy (TUSPLV) on recurrent varicocele (VC). In order to compare the surgical effects of TUSPLV to traditional retroperitoneal ligation of the internal spermatic vein, 64 patients with recurrent VC were enrolled and divided into the control group (n=30) and the observation group (n=34). Patients in the control group underwent surgery using traditional retroperitoneal ligation of the internal spermatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The outcome measures were spontaneous pregnancy, improvement in sperm parameters and complications (recurrence, hydrocele, testicular atrophy and infection–haematoma). As shown in Table , of the studies reporting treatment of recurrent varicocele, 21 (612 subjects) met the inclusion criterion, reporting at least one of the post‐treatment sperm parameters, spontaneous pregnancy and complication rates in adults and adolescents who underwent treatment for recurrent varicocele (Çayan & Akbay, ; Chawla et al, ; Chen, ; Çift & Yucel, ; Feneley et al, ; Flati et al, ; Glassberg et al, ; Grober et al, ; Guevara et al, ; Jargiello et al, ; Kaufman et al, ; Kenawi, ; Kim et al, ; Lund & Jensen, ; Madjar et al, ; Mazzoni et al, ; Moon et al, ; Niedzielski et al, ; Punekar et al, ; Sze et al, ; Yan et al, ). Interventions were divided into surgical (open or laparoscopic) and radiological (sclerotherapy or embolisation) groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome measures were spontaneous pregnancy, improvement in sperm parameters and complications (recurrence, hydrocele, testicular atrophy and infection–haematoma). As shown in Table , of the studies reporting treatment of recurrent varicocele, 21 (612 subjects) met the inclusion criterion, reporting at least one of the post‐treatment sperm parameters, spontaneous pregnancy and complication rates in adults and adolescents who underwent treatment for recurrent varicocele (Çayan & Akbay, ; Chawla et al, ; Chen, ; Çift & Yucel, ; Feneley et al, ; Flati et al, ; Glassberg et al, ; Grober et al, ; Guevara et al, ; Jargiello et al, ; Kaufman et al, ; Kenawi, ; Kim et al, ; Lund & Jensen, ; Madjar et al, ; Mazzoni et al, ; Moon et al, ; Niedzielski et al, ; Punekar et al, ; Sze et al, ; Yan et al, ). Interventions were divided into surgical (open or laparoscopic) and radiological (sclerotherapy or embolisation) groups.…”
Section: Methodsmentioning
confidence: 99%
“…Recurrent varicoceles can be treated via open redo surgical, radiologic and laparoscopic approaches (Çayan & Akbay, ; Chawla, Kulkarni, Kamal, & Zini, ; Chen, ; Çift & Yucel, ; Feneley, Pal, Nockler, & Hendry, ; Flati et al, ; Glassberg et al, ; Grober, Chan, Zini, & Goldstein, ; Guevara, El‐Hilal, & Darcy, ; Jargiello et al, ; Kaufman et al, ; Kenawi, ; Kim et al, ; Lund & Jensen, ; Madjar, Moskovitz, Issaq, Weinberger, & Nativ, ; Mazzoni, Minucci, & Gentile, ; Moon, Cho, Kim, Park, & Park, ; Niedzielski & Paduch, ; Punekar, Prem, Ridhorkar, Deshmukh, & Kelkar, ; Sze et al, ; Yan, Wu, & Wang, ). Recurrent varicoceles have been previously treated with radiological methods, because of redo surgical complications, including testicular atrophy, hydrocele and nerve injury (Feneley et al, ; Guevara et al, ; Jargiello et al, ; Kaufman et al, ; Kim et al, ; Mazzoni et al, ; Punekar et al, ; Sze et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocele formation, testicular artery injury, vascular and abdominal organ injury, and infection were reported in the retroperitoneal series with an incidence of 10%, 3%, 10%, and 6% respectively (Yan et al, 2017). Whereas in the laparoscopic technique the risks of Hydrocele formation, testicular artery injury, vascular and abdominal organ injury, and infection was 3% for all (Yan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven articles, four evaluated the outcome of micro surgical technique (Cayan & Akbay, 2018;Chen, 2014;Grober et al, 2004;Madjar et al, 1998), two the radiological approach (Punekar et al, 1996;Sze et al, 2008) and one looked for both open retroperitoneal and laparoscopic surgery (Yan et al, 2017). Quality assessment revealed that two studies were of good quality (9 stars) (Cayan & Akbay, 2018;Chen, 2014), while the remaining studies were of fair quality (5-6 stars).…”
Section: Meta-analysismentioning
confidence: 99%
“…Overlooking small internal spermatic veins, especially during macroscopic surgery which later become dilated, are the disadvantages of macroscopic surgery [11] , it is still controversial which treatment is to be preferred for recurrent varicocele. Although microsurgery, embolization, and laparoscopic surgical methods are preferable methods for varicocele recurrence, varicocelectomy with microsurgical method is the recommended treatment modality due to its lesser number of side effects and complications [12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%